Examining the Awareness of Halal Logo and the Confidence Level of Malaysian for Thailand Halal Products - Jamal Abdul Nassir Shaari; Muhammad Khalique; Mohd Khairul Hisyam Hassan (Allied Business Academics, 2024)
Non-Indexed Publication